APLIKASI EDUKASI PLANET BERBASIS ANDROID - Clara Hetty Primasari (Institut Teknologi Dirgantara Adisutjipto, 2017)
Indonesia is one of the countries which the numbers of mobile phone number users exceed its population. Most of them choose mobile phones with android operating system. This fact opens opportunities for application developers to develop applications for a variety of purposes by using android as their platform. This research aims to make Physics educational application especially for Planet material for Senior High School. Learning process which previously using material from a textbook is converted to an android application form so anyone who has android phone can access this material and be able to learn wherever and whenever they want. This educational application displays material using text and picture and contents inside it are tailored to the applicable senior high school curriculum and at the end, there are some multiple choice evaluation questions that can directly provide feedback to users who have answered the question. Test results from this educational application indicate that this application has been well received, both in the aspect of ease of use and conformity with the curriculum and otherwise useful to enrich the learning experience of physics, especially about the Planet.